2020
DOI: 10.1007/s43452-020-00050-0
|View full text |Cite
|
Sign up to set email alerts
|

Research on temperature action and cracking risk of steel–concrete composite girder during the hydration process

Abstract: Temperature changes due to hydration heat often cause cracks in the early-age concrete deck of steel-concrete composite girder bridges, even before opening to traffic. However, no available methods are provided in current specifications for the thermal effect calculation. To fill this gap, large-scale temperature measurements and fine finite-element model (FEM) analysis were performed on an actual composite girder bridge. Based on the fully validated FEM, a comprehensive parametric study was carried out to est… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…Another temperature study on steel-concrete compositing beams is cracking risk of steel-concrete composite girder during the hydration process. Liu et al (2020) reported a simplified method for the thermal stress calculation of composite girders. The measurements showed that temperature differences in the concrete deck varied and were below 5°C, and was less than that in the entire composite section.…”
Section: Introductionmentioning
confidence: 99%
“…Another temperature study on steel-concrete compositing beams is cracking risk of steel-concrete composite girder during the hydration process. Liu et al (2020) reported a simplified method for the thermal stress calculation of composite girders. The measurements showed that temperature differences in the concrete deck varied and were below 5°C, and was less than that in the entire composite section.…”
Section: Introductionmentioning
confidence: 99%
“…The strain distribution along the longitudinal axis of the raft, as depicted in Figure 8, was predominantly instigated by temperature fluctuations during the thermal accumulation phase (Liu et al, 2020). As discernible from Section 3.1, the temperature in the central region was typically superior to the surface and bottom, inducing a more pronounced expansion of its concrete volume.…”
Section: Principle Of Strain Distributionmentioning
confidence: 89%
“…Chen et al (2000) studied the temperature field of CFST columns and pointed out the size of the tube would affect the temperature evolutions. Liu et al (2020) analyzed the temperature field of two CFST columns subject to solar radiation. It was found that the temperature field of the concrete was unsymmetrical, and the temperature at the centroid was apparently higher than the mean temperature of the whole cross-section.…”
Section: Introductionmentioning
confidence: 99%